Management consulting career entry In-depth overview & strategic analysis of the critical recruitment factors with special emphasis on CEMS graduates - Levrincová, Alexandra; Hnilica, Jiří, 1976-; Šabata, Ondřej; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2012)
Recruitment process of any selected company calls the attention of almost every current graduate. The thesis looks closely on a specific recruiting process in management consulting, analyzes its key recruitment factors, tests them among the students from University of Economics, Prague and provides recommendations to two main stakeholders; the university and the students. The theoretical part of the work deals with the general information about consulting, outlines the development of the industry, describes its main players and points out the detailed recruiting process step by step to benefit any potential candidate. The practical part focuses on a qualitative and quantitative research among the students from different faculties at VSE which tested the general profiles of the students with special emphasis on CEMS graduates. The analyzed results showed clear outcomes upon which I was able to provide recommendations for improvement to the stakeholders.
Vedoucí práce: Jiří Hnilica
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses